2017
DOI: 10.1016/j.bjane.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of sugammadex for caesarean section in a patient with myasthenia gravis

Abstract: Myasthenia gravis is an autoimmune disorder that is characterized by muscle weakness that fluctuates, worsening with exertion, and improving with rest. Diagnosis of myasthenia gravis is made following clinical and physical examination and is confirmed by serum immunoassays to measure autoantibody levels. Myasthenia gravis especially when associated with pregnancy is a high-risk disease, and its course is unpredictable. We described the second report about use of sugammadex after rocuronium for a caesarean deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Therefore, many studies and case presentations have reported that an adequate muscle relaxation can only be achieved by inhalation agents. However, upon the availability of sugammadex, results indicate safe use of rocuronium in this group of patients [15,16].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, many studies and case presentations have reported that an adequate muscle relaxation can only be achieved by inhalation agents. However, upon the availability of sugammadex, results indicate safe use of rocuronium in this group of patients [15,16].…”
Section: Discussionmentioning
confidence: 98%
“…In patients with severe disease who are at higher risk of recurrent exacerbation during pregnancy, adjunct steroids and rituximab maybe started during their ICU course if prolonged hospitalization is expected and maternal benefit outweighs the risk. Steroids are associated with small (<1%) risk of cleft palate and rituximab with transient decline in B-cell counts, though data is very limited for rituximab and is generally not recommended [ 68 , 71 ].…”
Section: Medical and Surgical Managementmentioning
confidence: 99%
“…Pre-eclampsia (PE) presents a unique challenge in this population as magnesium, the treatments of choice for seizure prophylaxis in PE, is contraindicated in MG [ 71 , 73 ]. Thus, levetiracetam, valproic acid, and diazepam have all been used for seizure prophylaxis in these mothers.…”
Section: Medical and Surgical Managementmentioning
confidence: 99%
“…Treatment of patients with myasthenia gravis consists of : administration of oral medication, immunomodulating treatment by removal of AChR-ab through plasmapheresis or surgical intervention (thymectomy) [6,7].…”
Section: Abstract: Myasthenia Gravis Achr-ab Thymectomy Acetylcholinementioning
confidence: 99%